A Virtual Reality System for Training Operators - Patrão, Bruno (2013)
This paper presents an immersive system for virtual reality-based training of operators. Recent studies show that virtual reality simulations may be helpful in different fields, namely, industry and education. In this particular case we present a simulator for the training of tower cranes operators reducing their costs and risks. This immersive system integrates real-time 3D computer graphics with other modalities, such as, user pose tracking, stereoscopic headmounted display, pendant remote controller, physics behaviour, and spatial sound, in order to create a more realistic and immersive experience to the user. The results demonstrate two different simulator setups, one fixed and one portable, where the fixed offer a larger traceable area and the portable can be moved wherever is needed. The simulator is robust, reliable and provides an experience very similar to reality. Furthermore, it is possible to extend the simulation to other types of cranes and different types of scenarios.